2007
DOI: 10.1182/blood.v110.11.3815.3815
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Indices as Screening Tests for Beta-Thalassemic Trait.

Abstract: Introduction: The two most frequent microcytic anemias are β-thalassemic trait (β-TT) and iron deficiency anemia (IDA). Several discrimination indices have been proposed in order to distinguish between these two conditions. These indices are derived from several simple red blood cell indices, like RBC count, mean cell volume and RBC distribution width (RDW), as these are provided by electronic cell counters. Purpose of the study is to examine the diagnostic accuracy of six discrimination indices in the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
5
12
0
1
Order By: Relevance
“…We find the diagnostic efficiency of RET-Y quite similar to RBC-Y. The Green and King index meanwhile had a sensitivity of 75%, at a specificity level of 71% which would generally be in agreement with previous studies where the sensitivity for discrimination of BTT from IDA was in the region of 70-75% (Ntaios et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find the diagnostic efficiency of RET-Y quite similar to RBC-Y. The Green and King index meanwhile had a sensitivity of 75%, at a specificity level of 71% which would generally be in agreement with previous studies where the sensitivity for discrimination of BTT from IDA was in the region of 70-75% (Ntaios et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Iron deficiency anaemia (IDA) may however show red cell indices quite similar to that seen with thalassaemias and haemoglobin variants with substantial overlaps especially as the prevalence of IDA tends to be high in the same populations. Various combinations of red cell indices have been proposed in order to allow better discrimination between IDA and the thalassaemias (Beyan, Kaptan & Ifran, 2007;Ntaios et al, 2007;Sirdah et al, 2008). This would allow optimization of cost-effectiveness as only patients that require further investigations for thalassaemias and haemoglobin variants need to be subjected to costly HPLC and genetic testing.…”
Section: S U M M a R Ymentioning
confidence: 99%
“…The author evaluated the efficiency of this index in 110 IDA patients and 150 b-TT patients and found that it has sensitivity of 100%, specificity of 88.5% and discriminant efficiency of 92.3% for screening b-thalassemia minor at a cut-off value of 3.5. These results are comparable with other previously reported erythrocytic indices (Beyan, Kaptan & Ifran, 2007;, 2008a and show that this new ratio may be useful for the differential diagnosis of microcytosis.…”
supporting
confidence: 91%
“…Many discriminant formulas have been published that are based on red cell parameters only and that can provide a reasonable or good indication whether thalassemia is a likely cause of microcytosis [1][2][3][4][5]. In that way, additional tests may be selected for the most efficient diagnostic strategy.…”
Section: Introductionmentioning
confidence: 99%